Short-Time Work and Unemployment in and after the Great Recession. Issue 4 (22nd January 2021) - Kopp, Daniel; Siegenthaler, Michael
Abstract: We study whether the Swiss short-time work (STW) program reduced unemployment in and after the Great Recession using quarterly establishment-level panel data linking administrative data sources. We compare changes in layoffs into unemployment, employment, and establishment survival between establishments that applied successfully and establishments that applied unsuccessfully for STW at cantonal employment agencies. The unsuccessful establishments provide a valid counterfactual for the successful ones because cantonal approval practices are partly idiosyncratic. We find that STW increases establishment survival and prevents rather than postpones dismissals. The 7, 857 establishments treated in 2009 would have dismissed 20, 600 additional workers into unemployment (0.47% of the labor force) until 2012. Most workers would have been dismissed in the quarters immediately following the application, and more than a third would have become long-term unemployed. The savings on unemployment benefits may have compensated for the spending on STW benefits.